PERANCANGAN KOMUNIKASI VISUAL KAMPANYE DIGITAL PELESTARIAN CERITA RAKYAT INDONESIA PADA ANAK “CERITA DARI” - Saputra, Hendra; A.B, Nandang Wahyu (Anggada : Jurnal Desain dan Seni, 2020)
"Cerita Dari" is a digital campaign that strives to preserve Indonesian folklore. This digital campaign includes designs on various social media platforms such as Instagram, Twitter, and YouTube. The design of the structure itself is made according to a strategy that is suitable to be applied in each social media platform. Besides that, although each platform has a different plan, each of these platforms is still continuous with one another, namely communicating the "Cerita Dari" campaign. This design will follow the flow of the campaign phase that has been determined, from the first phase, namely "Campaign Introduction," which explains the creation of this campaign from the beginning, such as logos, fonts, ornament, and colors. Then the second phase is the "Communication Phase" phase, where the initial communication of this campaign will be like and using any media. The last phase is the "Maintaining Phase," the phase where you maintain the communication made by doing the main media that can attract the audience's attention for a certain period.